2021
DOI: 10.3389/fonc.2021.653491
|View full text |Cite
|
Sign up to set email alerts
|

The Clinical Significance and Prognostic Value of HER2 Expression in Bladder Cancer: A Meta-Analysis and a Bioinformatic Analysis

Abstract: ObjectiveHuman Epidermal Growth Factor Receptor 2 (HER2) is highly expressed in multiple malignancies and associated with patients’ prognosis, but its role in bladder cancer (BCa) remains elusive. We conducted this meta-analysis to explore the clinical significance and prognostic value of HER2 in BCa.MethodsPubMed was searched for studies published between January 1, 2000 and January 1, 2020. The odds ratios (ORs) and hazard ratios (HRs) with 95% confidence intervals (95%CIs) were used to investigate the relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 53 publications
(94 reference statements)
3
23
0
Order By: Relevance
“…The association between clinical outcomes and HER2 expression in UCB has been reported in several single-center studies; however, the overall result remains controversial. Recently, Gan et al ( 30 ) comprehensively analyzed 14 studies that included a total of 1,398 patients with BCa with regard to the HER2 status determined using IHC. They found that the overexpression of HER2 was strongly related to an advanced pathological stage, high tumor grade and tumor recurrence, but not to OS, disease-specific survival, or progression-free survival.…”
Section: Discussionmentioning
confidence: 99%
“…The association between clinical outcomes and HER2 expression in UCB has been reported in several single-center studies; however, the overall result remains controversial. Recently, Gan et al ( 30 ) comprehensively analyzed 14 studies that included a total of 1,398 patients with BCa with regard to the HER2 status determined using IHC. They found that the overexpression of HER2 was strongly related to an advanced pathological stage, high tumor grade and tumor recurrence, but not to OS, disease-specific survival, or progression-free survival.…”
Section: Discussionmentioning
confidence: 99%
“…and ATM in bladder carcinogenesis individually. 18,46,47 Published data reported amplification of the ERBB2 gene in up to 42% and up-regulation of protein expression in up to 30% of bladder cancer cases. The same report indicated an inactivating mutation of ATM gene in 14% of bladder cancers.…”
Section: Discussionmentioning
confidence: 99%
“…One trial (NCT03740256) combines the use of a human epidermal growth factor receptor 2 (HER2)–specific CAR T with an immunostimulatory oncolytic virus to enhance immune reactivity. HER2 has been found to be altered in bladder cancer and in a study was found to be altered in 16% of bladder tumors 62,63 . Overall, CAR T cells for the treatment of bladder cancer are in the early stages of clinical development and target antigens that are overexpressed in bladder tumors.…”
Section: Act In Bladder Cancermentioning
confidence: 97%
“…HER2 has been found to be altered in bladder cancer and in a study was found to be altered in 16% of bladder tumors. 62,63 Overall, CAR T cells for the treatment of bladder cancer are in the early stages of clinical development and target antigens that are overexpressed in bladder tumors.…”
Section: Car T Cellsmentioning
confidence: 99%